2014
DOI: 10.1007/s10936-014-9325-3
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent Frequency Effects on Anaphoric Pronoun Resolution: Evidence from Spanish

Abstract: High-frequency words are usually understood and produced faster than low-frequency words. Although the effect of word frequency is a reliable phenomenon in many domains of language processing, it remains unclear whether and how frequency affects pronominal anaphoric resolution. We evaluated this issue by means of two self-paced reading experiments. Native speakers of Spanish read sentences containing the anaphoric noun or pronoun at the subject syntactic position (Experiment 1) or at the object syntactic posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Several recent studies have reported that less frequent antecedents lead to faster reading times at the pronoun (van Gompel & Majid, 2004), or to no reliable differences at the pronoun (Egusquiza et al, 2016;Lago, 2014). However, each of these studies is crucially different from ours in several aspects.…”
Section: Our Results In Light Of Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have reported that less frequent antecedents lead to faster reading times at the pronoun (van Gompel & Majid, 2004), or to no reliable differences at the pronoun (Egusquiza et al, 2016;Lago, 2014). However, each of these studies is crucially different from ours in several aspects.…”
Section: Our Results In Light Of Previous Literaturementioning
confidence: 99%
“…In languages with grammatical gender, this information may be morphological information (Cacciari, Carreiras & Barbolini Cionini, 1997); but also, lexemic properties such as length and frequency of a word (Simner & Smyth, 1999;Duffy & Rayner, 1990). Thus, we predict that "it" should be sensitive to frequency and length of the preceding linguistic material resolution (although see Egusquiza, Navarrete &Zawiszewski, 2016, andLago, 2014, for failure to find frequency effects with personal pronouns).…”
Section: Current Studies and Predictionsmentioning
confidence: 89%
“…A barrier in resolving this debate is that the studies that support the different hypotheses diverge widely in their methodology. Most of the studies supporting “full access” were based on production (Finocchiaro & Caramazza, 2006; Navarrete, Basagni, Alario, & Costa, 2006), and there have been far fewer studies examining comprehension, which have produced mixed findings (Egusquiza et al, 2016; Heine, Tamm, Hofmann, Bösel, & Jacobs, 2006; Simner & Smyth, 1999; van Gompel & Majid, 2004). Future studies with bilingual readers can offer a more sensitive test of whether a referent’s lexical representation is reaccessed, because there are lexical relationships across languages that do not exist within a single language, such as the existence of cognates and interlingual homographs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is an ongoing debate in the literature on anaphoric processing that could benefit from a systematic examination of the effects of cognate status of referents on anaphor processing. Specifically, there are different hypotheses regarding what lexical features of an anaphor's referent, if any, are reaccessed when the anaphor is encountered (Egusquiza, Navarrete, & Zawiszewski, 2016). According to the "full access hypothesis," the full lexical representation of a referent is reaccessed when an anaphor is encountered.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Desde o estudo seminal de Gordon et al (1993) várias pesquisas psicolinguísticas têm focalizado a PNR em várias línguas. Essa penalidade entre pronome pleno e nome repetido foi confirmada em outros estudos realizados em Inglês (GORDON e CHAN, 1995;CHAMBERS e SMYTH 1998;KENISSON e GORDON, 1997), em Francês (ERNST, 2007), em Chinês Mandarim (YANG et al, 1999), em Espanhol (EGUSQUIZA et al, 2016) e em Japonês (SHOJI et al, 2017). Entretanto, esse efeito não foi encontrado em estudos realizados em Espanhol Argentino (GERLOMINI-LEZAMA, 2008, 2010 e em Português Brasileiro/PB (MAIA e CUNHA LIMA, 2011LIMA, , 2012MAIA, 2013;LIMA, 2015;ALMOR et al, 2017), contrastando com as pesquisas conduzidas por Leitão e colaboradores (LEITÃO, 2005; QUEIROZ e LEITÃO, 2008;LEITÃO e SIMÕES, 2011;LEITÃO, RIBEIRO e MAIA, 2012) 1.1 Estudos sobre a penalidade do nome repetido em Português Brasileiro O estudo pioneiro em Português Brasileiro (PB) de processamento correferencial focalizando a Penalidade do Nome Repetido (PNR) foi realizado por Leitão (2005) em sua tese de doutorado.…”
unclassified